2015
DOI: 10.1111/ics.12287
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress – a key emerging impact factor in health, ageing, lifestyle and aesthetics

Abstract: Oxidative stress is the resultant damage that arises due to redox imbalances, more specifically an increase in destructive free radicals and reduction in protection from antioxidants and the antioxidant defence pathways. Oxidation of lipids by reactive oxygen species (ROS) can damage cellular structures and result in premature cell death. At low levels, ROS-induced oxidative stress can be prevented through the action of antioxidants, however, when ROS are present in excess, inflammation and cytotoxicity eventu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 87 publications
1
63
0
1
Order By: Relevance
“…UVB can also be directly absorbed by DNA, leading to direct induction of damage within cells. Mitochondrial DNA is particularly vulnerable to damage following exposure to UVR as mitochondria have limited DNA repair mechanisms [8]. A recent study looking at the action spectrum of UVR-induced mitochondrial damage showed that mitochondrial DNA is more vulnerable to damage at UVR wavelengths >320 nm when compared with nuclear DNA [25].…”
Section: Sunlightmentioning
confidence: 99%
See 4 more Smart Citations
“…UVB can also be directly absorbed by DNA, leading to direct induction of damage within cells. Mitochondrial DNA is particularly vulnerable to damage following exposure to UVR as mitochondria have limited DNA repair mechanisms [8]. A recent study looking at the action spectrum of UVR-induced mitochondrial damage showed that mitochondrial DNA is more vulnerable to damage at UVR wavelengths >320 nm when compared with nuclear DNA [25].…”
Section: Sunlightmentioning
confidence: 99%
“…This is of particular importance as there is increasing evidence that alterations in mitochondrial function can adversely impact skin health and lead to skin disease [26]. UVR is therefore able to increase oxidative stress by both direct and indirect means, either by potent stimulation of ROS or by direct DNA damage [8]. This increase in oxidative stress can impair cellular functions, leading to the phenotypic manifestations of extrinsic skin ageing.…”
Section: Sunlightmentioning
confidence: 99%
See 3 more Smart Citations